👤

Svp aider moi c urgent

Svp Aider Moi C Urgent class=

Répondre :

1. C'est egal a 3x^2 - 6x + 3
car 3 × ( x - 1 ) × ( x- 1 )
= 3× ( x^2 - 2x + 1 )
= 3x^2 - 6x + 3

2. a (2x+1)(x-3) = 2x^2 - 5x - 3
b (3x+1)^2 = 3x^2 + 6x + 1
c (2x-5)^2 = 4x^2 - 20x + 25
d ( 5x-3)(5x+3) = 25x^2 - 9
d -2(2x+3)^2 = -8x^2 - 24x - 18
e 3(x-5)(x+2) = 3x^2 - 9x - 30

3. a (x^2 - 3x) = x(x-3)
b (25 - 16t^2) = -( 4t-5)(4t+5)
c 9x^2 - 12x + 4 = (3x-2)^2
d 2t^2 - 4t + 2 = 2(t-1)^2

4. 3x^2 + 3x -6

5. positif ou nul pour tout x